Mental Health Intervention in the Digital Age - Camelia Bakker (Medical Studies and Health Journal (SEHAT), 2024)
This study aims to investigate the role of digital technology in mental health interventions through a systematic literature review. His background includes the emergence of digital technology as an innovative solution to providing more affordable and accessible mental health care. The research method used is a systematic literature review of related articles in scientific databases. The results of the discussion show that digital technologies, such as mobile applications, online platforms, virtual reality, and augmented reality, offer various advantages in increasing the accessibility, scalability, and effectiveness of mental health care. The implication of this research is that digital technology can be a powerful tool in helping individuals manage their own mental wellbeing, while remaining mindful of ethics, data security and the need for person-centred interventions.